INVASI PASUKAN KOALISI: KEBANGKITAN ATAU KETERPURUKAN KEHIDUPAN SOSIAL-POLITIK PEREMPUAN IRAK - Hafiza Aryaputri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
Iraq once touted as the Middle Eastern country that offers freedom to women. However, the fall of Saddam's regime in April 2003 by the Coalition Forceshas brought the Iraqi women in to uncertain change. One of the Coalition Forces agenda to Iraqwas to set UN Security Council Resolution No.1483 to improve the lives of Iraqi women in a stable democratic system. But until the withdrawal of Coalition Forces in 2011, the lives of women in Iraq remain decayed. The purpose of this study was to assess descriptively the changes occured in Irak under the regime of Saddam Hussein (1979-2003) and under the Coalition Forces invasion (2003-2011).Methodused was qualitative approach by interviewing some Iraqi emigrants in Malaysia with additional of literature review. Result of this study showed that women conditions in Iraq during the invasion has worsened. Even some Iraqis claimed prefer to live in Saddam’s erarather than the time of Coalition Forces presence.